KOMPARASI INTERIOR RUMAH TRADISIONAL NUSANTARA: RUMAH JOGLO YOGYAKARTA INDONESIA DAN RUMAH MELAKA MALAYSIA - Swastika Dhesti Anggriani; Ponimin -; Lisa Sidyawati; Norsidah Ujang (LP2M ISBI Bandung, 2023)
This study aims to determine the differences and similarities between traditional houses in Nusantara with research samples taken from 2 countries namely Joglo traditional hoise in Yogyakarta Indonesia and Melaka traditional house in Melaka Malaysia. The research method used is qualitative by means of descriptive research that takes the type of comparative activities of traditional house in Nusantara. Data obtained from direct observation to the location (Yogyakarta and Malaysia), interviews with informants, and taking documents data in the form of photos, layout drawings, and images. The results showed similarities and differences between the Joglo traditional house in Yogyakarta, Indonesia and the Melaka tarditional house in Malaysia. Judging from the aspect of the building, the Joglo house was built directly above ground level while the Melaka house was built with a stage system. The different types of buildings, plus the different users and spatial activities, lead to differences in interior layout. However, both Joglo traditional house and Melaka traditional house were built in 1 building mass. Both houses also still use wood material in some parts of the house. In addition, the house is also supported by poles that use wood material. Keyword: Comparation, Interior, Traditional House, Joglo, Melaka Penelitian ini bertujuan untuk mengetahui perbedaan dan persamaan diantara rumah tradisional Nusantara dengan sampel penelitian yang diambil dari 2 negara yaitu rumah tradisional Joglo Yogyakarta Indonesia dan rumah tradisional Melaka Malaysia. Metode penelitian yang digunakan adalah kualitatif dengan cara penelitian deskripsi yang mengambil jenis kegiatan komparasi rumah tinggal tradisional Nusantara. Data diperoleh dari observasi langsung ke lokasi (Yogyakarta dan Malaysia), wawancara kepada narasumber, serta mengambil data dalam bentuk dokumen berupa foto, gambar layout, dan gambar tampak. Hasil penelitian menunjukkan adanya persamaan dan perbedaan antara rumah Joglo Yogyakarta, Indonesia dan rumah Melaka Malaysia. Ditinjau dari aspek bangunan, rumah Joglo dibangun langsung di atas permukaan tanah sedangkan rumah Melaka dibangun dengan sistem panggung. Perbedaan jenis bangunan ini, ditambah perbedaan pengguna dan aktivitas ruangnya, menyebabkan adanya perbedaan tata ruang interior di dalamnya. Akan tetapi, Baik rumah Joglo dan Rumah Melaka dibangun dalam 1 massa bangunan. Kedua rumah tersebut juga masih menggunakan material kayu di beberapa bagian rumah. Selain itu, rumah juga disangga oleh tiang yang menggunakan material kayu. Keyword: Komparasi, Interior, Rumah Tradisional, Joglo, Melaka